Discovering the Tourism Sensory Experience in Melaka UNESCO WHS - Abd Rahman, Nur Hidayah; Scott, Noel; Ismail, Hairul Nizam (Springer Nature Switzerland AG, 2023)
The ‘Tourism Experience’ studies have highlighted the importance of sensory experience since the tourists engage with a destination and understand that particular place based on their senses: sight, taste, hearing, smell, and touch. Previously, most of the studies focused on the visual sense, gustatory sense and auditory sense, especially in agriculture tourism, gastronomy tourism and nature-based tourism. However, the tourism sensory experience of urban heritage destinations has not been addressed adequately. This paper explores the elements of sense-making in Melaka UNESCO World Heritage Site (WHS), Malaysia. The paper uses a combination of systematic review of the relevant literature and content analysis of brochures and other publications to identify sensory elements used in describing cultural heritage experiences in Melaka UNESCO WHS, Malaysia. The contributions of this study are i) the sensory experiences are influenced by the destination ‘theme’, ii) both positive and negative sensory impressions are associated with a heritage experience, and iii) a systematic review of past publications and subsequent content analysis method used here provides a useful technique for understanding the tourism sensory experience of an attraction.